Akurasi Data Koordinat Atlas Der Gehele Aarde Dalam Penentuan Arah Kiblat: Studi Kasus BHRD Kabupaten Tegal - Naelul Marom; Ahmad Izzuddin (Astroislamica: Journal of Islamic Astronomy, 2025)
The determination of the Qibla direction in Indonesia ideally utilizes precise local coordinate data. However, the Board of Hisab and Rukyat (BHRD) of Tegal Regency employs a unique method by using coordinate data derived from the "Atlas Der Gehele Aarde," a Dutch colonial-era atlas, combined with a "Two Compass Method." This study aims to evaluate the accuracy of Qibla measurements resulting from this method and to analyze it from the perspectives of Falak science (astronomy) and Islamic law (Fiqh). This research is a field study using a qualitative approach. Data were collected through interviews with BHRD officials and direct verification measurements at five sample mosques using a Theodolite and Google Earth data. The results indicate a discrepancy between the BHRD calculations and modern astronomical measurements. The use of single-city coordinates from the Atlas and the neglect of magnetic declination in the compass method resulted in a Qibla deviation ranging from 1° to 2° 35'. Astronomically, this deviation is considered inaccurate as it exceeds the tolerance limit of 0° 42'. However, from the perspective of Islamic Law, particularly the Shafi'i school, these measurements remain legally valid (sah) under the concept of 'jihat al-ka'bah' (general direction) based on 'dzan' (strong assumption) for regions far from Mecca.